Use High Temperature as a Curing to Change Antibiotic Resistance of Salmonella Typhi - Sura Mohammed Sachit (Journal of Global Pharma Technology, 2018)
Gradual growing levels of antibiotic resistance in the developing countries had incurably increased in the last few decades as a consequence of evolutionary microbial characters and random antibiotic use. Many important clinical pathogens showed multiple resistances to many different antibiotics, this means any dangerous infection that can easily transfer from any country to any other, representing global increasing problem. Typhoidal Salmonellae represents interesting concern for world public health, especially fever caused by Salmonella typhi which cause different blood stream infection .Seven clinical isolates of Salmonella typhi were isolated and identified biochemically from a hospital in Baghdad. They had multiple resistances to Cefepime, Imipenem, Amikacin, Norfloxacin, Floxacin and Ceftazidime. The isolates appeared different elimination of multiple antibiotic resistances character after incubation at high temperature (45ºC), meaning the isolates lose antibiotic resistance plasmids after physical treatment by high temperature. This simple, inexpensive and safe treatment represents a promising way to eliminate antibiotic resistance character from many dangerous pathogenic bacteria. Keywords: Salmonella typhi, Antibiotic resistance, High temperature.